Penerapan Model Kooperatif Tipe Numbered Heads Together Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Pada Siswa SMP - Akase, Sisilia Fransisca; Machmud , Tedy; Pauweni, Khardiyawan A.Y. (FKIP Universitas Mataram, 2025)
This Classroom Action Research was conducted at SMP Negeri 2 Suwawa during the 2024/2025 academic year, with 23 students from class VIII-3 as the research subjects. This research aims to evaluate applying the cooperative learning model type Numbered Heads Together (NHT) can enhance students’ mathematical problem-solving skills in the topic of ‘systems of Linear Equations in Two-Variable.’ Data collection techniques included observations and test, with research instruments consisting of teacher activity observation sheets, student activity observation sheets, and essay test questions. The research results indicate that the cooperative learning model of the Numbered Heads Together type is effective in improving students' mathematical problem-solving abilities, as evidenced by the increase in the percentage of students’ mathematical problem-solving test results from 69.57% to 78.26%, the percentage of teacher activity observation sheets from 58.33% to 91.67%, and the percentage of student activity observation sheets also increased from 54.55% to 90.91%. Based on the data analysis, it can be concluded that implementing the cooperative learning model type Numbered Heads Together has significantly enhanced students’ mathematical problem-solving skills.